(untitled) (Innovative professional education, 2022)
The services of information and digital systems, which are now widely used to evaluate the effectiveness of the activities of scientific and scientific-pedagogical workers, divisions of higher education institutions and scientific institutions, are characterized. Attention is focused on presenting the profile of a scientific and scientific-pedagogical worker in social networks. The peculiarities of their use for the development of a scientific career are substantiated.